2009
DOI: 10.5424/sjar/2009073-443
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of bread-making quality of Spanish bread-wheat genotypes

Abstract: In this study, 36 Spanish wheat genotypes (five modern commercial cultivars, four cultivars introduced after the green revolution and 27 landraces from northwestern Spain) were evaluated. Grain (yield, specific weight, protein content and falling number) and flour (yield, protein content, Zeleny index, wet gluten and gluten index) properties were analyzed. Dough behaviour during mixing (DoughLAB) and handling (alveograph) was also considered. An evolution in grain and flour properties was observed over time. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Our results are a very good example illustrating that, if breeding programs pay more attention to protein quality instead of protein content, grain quality levels can be maintained or even increased while the grain yield is also growing. Gomez et al (2009) and Guarda et al (2004) showed similar conclusions in studies with Spanish and Italian materials, respectively. Uzik et al (2009) did not reach the same conclusion with winter wheats in Slovak Republic.…”
Section: Discussionsupporting
confidence: 78%
“…Our results are a very good example illustrating that, if breeding programs pay more attention to protein quality instead of protein content, grain quality levels can be maintained or even increased while the grain yield is also growing. Gomez et al (2009) and Guarda et al (2004) showed similar conclusions in studies with Spanish and Italian materials, respectively. Uzik et al (2009) did not reach the same conclusion with winter wheats in Slovak Republic.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast to breeders, millers often use the gluten index for estimating protein quality. We determined a moderately positive correlation of gluten index with SDSS ( r = 0.51, p < 0.01) and Z‐SDS ( r = 0.47, p < 0.01), respectively (Table 3), which is lower than values reported for durum (Clarke et al, 2010; Longin et al, 2013b) and bread wheat (Gómez et al, 2009; Bonfil et al, 2015). However, the heritability for gluten index was 0.55, and thus much lower than the heritability of Z‐SDS or SDSS of 0.90.…”
Section: Discussionmentioning
confidence: 57%
“…In general, the best correlations have been obtained when analysing the rheological characteristics of doughs, since these characteristics are very dependent on the characteristics of gluten proteins. These characteristics, in turn, are determined by the culture conditions and milling system, but principally by genetic factors 2, 5, 6…”
Section: Introductionmentioning
confidence: 99%